ONE STAGE BILATERAL KNEE AND HIP ARTHROPLASTIES IN 42 YEARS OLD FEMALE - Aziz, Amer; Javed, Shahzad; Ahmed, Ashfaq; Dogar, Ammar; Ahmad, Saeed; Akram, Rizwan; Amin, Qazi Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Knee and hip joint replacement surgeries are the mainstay of treatment in patients having grade 3 or grade 4 arthritis either due to degenerative process, rheumatoid disease or due to some other disease process. The main aim of these surgeries are to decrease the morbidity, early rehabilitation and decrease management costs of such patients. We report the first case in which bilateral total knee and total hip replacement surgery were done in single anaesthesia in 42 years old female patient suffering from Rheumatoid Arthritis. Keywords: Rheumatoid Arthritis; Arthroplasties; One Stage; Bilateral